2016
DOI: 10.1371/journal.pone.0154968
|View full text |Cite
|
Sign up to set email alerts
|

One-Class FMRI-Inspired EEG Model for Self-Regulation Training

Abstract: Recent evidence suggests that learned self-regulation of localized brain activity in deep limbic areas such as the amygdala, may alleviate symptoms of affective disturbances. Thus far self-regulation of amygdala activity could be obtained only via fMRI guided neurofeedback, an expensive and immobile procedure. EEG on the other hand is relatively inexpensive and can be easily implemented in any location. However the clinical utility of EEG neurofeedback for affective disturbances remains limited due to low spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 51 publications
(83 reference statements)
1
57
0
Order By: Relevance
“…If rtfMRI‐NF proves to be a successful treatment for ADHD, it could also be transferred to the cheaper NIRS‐NF which has already been piloted in ADHD [Marx et al, 2014] or to fMRI‐inspired EEG‐NF methods, which use concurrent fMRI‐EEG‐NF to establish the EEG correlates of localized fMRI BOLD activity for a better spatially informed EEG‐NF [Keynan et al, 2016; Meir‐Hasson et al, 2016]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If rtfMRI‐NF proves to be a successful treatment for ADHD, it could also be transferred to the cheaper NIRS‐NF which has already been piloted in ADHD [Marx et al, 2014] or to fMRI‐inspired EEG‐NF methods, which use concurrent fMRI‐EEG‐NF to establish the EEG correlates of localized fMRI BOLD activity for a better spatially informed EEG‐NF [Keynan et al, 2016; Meir‐Hasson et al, 2016]. …”
Section: Discussionmentioning
confidence: 99%
“…Although rtfMRI-NF is expensive, it could potentially achieve a high cost-benefit ratio over long-term pharmacotherapy for ADHD, which is costly, if it treats the underlying cause rather than symptoms of ADHD, reduces or eliminates medication treatment, and has longer-term efficacy and no side effects [Klora et al, 2016]. If rtfMRI-NF proves to be a successful treatment for ADHD, it could also be transferred to the cheaper NIRS-NF which has already been piloted in ADHD [Marx et al, 2014] or to fMRI-inspired EEG-NF methods, which use concurrent fMRI-EEG-NF to establish the EEG correlates of localized fMRI BOLD activity for a better spatially informed EEG-NF Meir-Hasson et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…As simulated ( Fig. 4c), spontaneous baseline activity of cortical areas organizes after several seconds to minutes without external stimuli 25,26 around ~8 Hz [27][28][29] . Brain coherence measurements without external stimuli 30,31 align well with the coherence patterns of simulated spontaneous activity in dependence of space and frequency ( Fig.…”
Section: Resultsmentioning
confidence: 76%
“…It is, therefore, important to note that our previous studies Meir-Hasson et al, 2016) clearly showed that volitional regulation of the amyg-EFP could be learned only when veritable feedback and not sham-feedback is provided. Another possible limitation regards the interface chosen for the transferability testing (skateboard visualization; Figure 1C).…”
Section: Discussionmentioning
confidence: 90%